A transient CFD research on the dynamic characteristics of liquid annular seals. (October 2018) - Xu, Rui; Hu, Yaoyu; Yin, Junlian; Zhang, Jiangtao; Wang, Dezhong
Abstract: In this paper, a transient CFD method has been proposed in predicting the dynamic characteristics of liquid annular seals and the reliability of the method is validated by comparing with the experiments of Kanemori and Iwatsubo. Dynamic characteristics of the liquid annular seals with different length have also been calculated. The results indicate that the principal stiffness of the annular seal can turn into negative from positive as the length of the seal increases, this phenomenon may change the force direction of the annular seal and affect the supporting conditions of the pump rotor.